2018
DOI: 10.1002/srin.201800337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single Power Two Circuits Electroslag Remelting Process on the Ingot Solidification Quality

Abstract: The laboratory experiments have been carried out to investigate the effects of different power supply circuits on the solidification quality of GCr15 manufactured by the single‐power, two‐circuit electroslag remelting process. According to the previous research, the different power supply circuits are named as conventional electroslag remelting withdrawal process (ESRW), single power two circuits electroslag remelting process (ESR‐STCCM) with up power process (ESR‐STCCM‐U) and down power process (ESR‐STCCM‐D),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…According to the previous study, 36) the shape of the molten metal pool has a directly effect on the removal of inclusions. Figure 13 is the result of the sulfur print experiment for different remelting processes, it is clearly demonstrated that the depths of the molten metal pool for the different processes are 152 mm and 85 mm, and the shape of the molten metal pool for ESR-STCCM is flatter and shallower (The effect of the remelting processes on the shape of the molten metal pool had been deeply discussed in our previous study 19) ). Therefore, ESR-STCCM is beneficial to the float process of the inclusions.…”
Section: Esr-stccmmentioning
confidence: 81%
See 2 more Smart Citations
“…According to the previous study, 36) the shape of the molten metal pool has a directly effect on the removal of inclusions. Figure 13 is the result of the sulfur print experiment for different remelting processes, it is clearly demonstrated that the depths of the molten metal pool for the different processes are 152 mm and 85 mm, and the shape of the molten metal pool for ESR-STCCM is flatter and shallower (The effect of the remelting processes on the shape of the molten metal pool had been deeply discussed in our previous study 19) ). Therefore, ESR-STCCM is beneficial to the float process of the inclusions.…”
Section: Esr-stccmmentioning
confidence: 81%
“…The details of the remelting processes had been described in our previous study. 19) When the slag and air interface (slagsurface) was submerging the up mould (Φ333 mm) more than 40 mm, the withdrawing operation was started. The remelting parameters were shown in Table 2.…”
Section: Esr Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the sulfur print experiment (Baumann method) was executed to reveal the pool profile. 17) The samples with the dimension of 10 mm × 10 mm × 10 mm were taken from the other half of the ingot at a distance of 130 mm from the bottom. The microstructures were displayed with the Lichtenegger and Bloesch etchant (20 g NH 4 HF, 0.5 g K 2 S 2 O 5 and 100 ml H 2 O) at room temperature after the standard polishing techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Cao et al [23] proposed that the primary heat source for the metal pool during the ESR process is molten slag and remelting droplets, and that the Joule heat (temperature) distribution within the metal pool has a significant effect on its morphology. Due to the mold wall's water-cooling effect, the Joule heat in the slag/ metal pool was concentrated in the central area.…”
Section: A Macrostructure Evolution and Mechanismsmentioning
confidence: 99%